Nasal Chemosensory-Stimulation Evoked Activity Patterns in the Rat Trigeminal Ganglion Visualized by In Vivo Voltage-Sensitive Dye Imaging - Rothermel, Markus (Public Library of Science, 2011)
Mammalian nasal chemosensation is predominantly mediated by two independent neuronal pathways, the olfactory and the trigeminal system. Within the early olfactory system, spatiotemporal responses of the olfactory bulb to various odorants have been mapped in great detail. In contrast, far less is known about the representation of volatile chemical stimuli at an early stage in the trigeminal system, the trigeminal ganglion (TG), which contains neurons directly projecting to the nasal cavity. We have established an in vivo preparation that allows high-resolution imaging of neuronal population activity from a large region of the rat TG using voltage-sensitive dyes (VSDs). Application of different chemical stimuli to the nasal cavity elicited distinct, stimulus-category specific, spatiotemporal activation patterns that comprised activated as well as suppressed areas. Thus, our results provide the first direct insights into the spatial representation of nasal chemosensory information within the trigeminal ganglion imaged at high temporal resolution.